Ticagrelor vs. Clopidogrel in Older Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention: Insights From a Real-World Registry - Zhang, Yunnan; Peng, Wenxing; Shi, Xiujin; Han, Jialun; Wang, Yifan; Fang, Zhenwei; Lin, Yang (Frontiers in Cardiovascular Medicine, 2022)
Background and objectives It is unclear whether more potent P2Y12 inhibitors are of benefit to older patients who are at a high risk for both ischemia and bleeding. We conducted an observational study to compare the clinical outcomes of clopidogrel and ticagrelor uses in older patients with acute coronary syndrome (ACS). Methods Older patients (aged ≥65 years) with ACS who underwent percutaneous coronary intervention were divided into clopidogrel-treated and ticagrelor-treated groups. The primary observational endpoint was the occurrence of net adverse clinical and cerebral events (NACCE) during a 12-month period, defined as the composite endpoint of all-cause death, myocardial infarction, stroke, stent thrombosis, urgent coronary revascularization, and clinically significant bleeding. The secondary endpoints were clinically significant bleeding and major adverse clinical and cerebral events (MACCE). Results This study included a total of 2611 patients. Of them, 1636 were received clopidogrel and 975 received ticagrelor. Between patients receiving clopidogrel and those receiving ticagrelor, no significant differences were noted in NACCE (8.4% vs. 9.7%, respectively; adjusted hazard ratio [HR], 0.86; 95% confidence interval [CI], 0.66–1.12) or MACCE (7% vs. 7%, respectively; adjusted HR, 1.13; 95% CI, 0.83–1.55) during the 12-month follow-up period. In contrast, the occurrence of clinically significant bleeding was significantly less in clopidogrel-treated patients compared with that in ticagrelor-treated patients (27, 1.7%, vs. 31, 3.2%, respectively; adjusted HR, 0.42; 95% CI, 0.25–0.69). Stratified analyses revealed no significant association between age (≥75 years vs. <75 years) and treatment condition in terms of primary or secondary endpoints. Conclusion This study showed that clopidogrel and ticagrelor had comparable net clinical benefits in patients with ACS aged ≥65 years. Additionally, clopidogrel was associated with a significantly lower risk of major bleeding than ticagrelor without an increase in ischemic risk. These findings suggest that clopidogrel is an effective alternative to the more potent P2Y12 inhibitor ticagrelor in older patients.